Crecimiento y absorcion de nutrientes del melon bajo invernadero - Rincon Sanchez, L.=700 1 Saez Sironi, J.; Perez Crespo, J.A.; Pellicer, C.; Gomez Lopez, M.D.
(Es, En)
ilus., 16 ref.
Keywords: CUCUMIS MELO; ABSORCION DE SUSTANCIAS NUTRITIVAS; CRECIMIENTO; CONCENTRACION; NITROGENO; FOSFORO; POTASIO; CALCIO; MAGNESIO; FERTIRRIGACION; ESPAÑA; MELON; MACRONUTRIENTES